2021
DOI: 10.1101/2021.08.05.21261634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long COVID in hospitalized and non-hospitalized patients in a large cohort in Northwest Spain, a prospective cohort study

Abstract: BackgroundSurvivors to COVID-19 have described long-term symptoms after acute disease. These signs constitute a heterogeneous group named long COVID or persistent COVID.ObjectiveThe aim of this study is to describe persisting symptoms six months after COVID-19 diagnosis in a prospective cohort in the Northwest SpainDesignThis is a prospective cohort study performed in the COVID-19 Cohort of Galicia Sur Health Institute (COHVID-GS).ParticipantsThis cohort includes patients in clinical follow-up in a health area… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Previous studies have reported lower prevalence rates of post-COVID-19 symptoms among nonhospitalized than hospitalized patients. 9,10,[13][14][15] Our results revealed similar proportions of hospitalized and nonhospitalized patients with post-COVID-19 symptoms 2 years after the acute infection, suggesting that, despite having not been hospitalized during the acute phase, the symptoms of long COVID are also found in the nonhospitalized cohort. This finding could be explained by the fact that COVID-19 severity is not a risk factor for the development of long COVID symptoms.…”
Section: Jama Network Open | Infectious Diseasessupporting
confidence: 64%
See 2 more Smart Citations
“…Previous studies have reported lower prevalence rates of post-COVID-19 symptoms among nonhospitalized than hospitalized patients. 9,10,[13][14][15] Our results revealed similar proportions of hospitalized and nonhospitalized patients with post-COVID-19 symptoms 2 years after the acute infection, suggesting that, despite having not been hospitalized during the acute phase, the symptoms of long COVID are also found in the nonhospitalized cohort. This finding could be explained by the fact that COVID-19 severity is not a risk factor for the development of long COVID symptoms.…”
Section: Jama Network Open | Infectious Diseasessupporting
confidence: 64%
“…Data on nonhospitalized patients are based on follow-up periods no longer than 6 months 9,10,[13][14][15] ; accordingly, we cannot directly compare our results with previous data. Previous studies have reported lower prevalence rates of post-COVID-19 symptoms among nonhospitalized than hospitalized patients.…”
Section: Jama Network Open | Infectious Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…There are similarities between our study, Living Risk Prediction Algorithm (QCOVID) study [ 21 ], and other reports [ 3 , 24 ] regarding sociodemographic and comorbidity variables associated with mortality. These include cardiometabolic conditions (eg, CKD, type 2 diabetes, ischemic heart disease, and atrial fibrillation), chronic obstructive pulmonary disease, and asthma.…”
Section: Discussionsupporting
confidence: 67%
“…2 Though PASC is more common in hospitalized patients, epidemiological studies suggest that over a third of non-hospitalized patients without clinically severe infection, may also get PASC. 3,4 Rough first estimates suggest that as much as 30% of the SARS-CoV-2 health burden could be due to infection-induced disability and PASC, not death, with the overall economic cost of PASC reaching half the cost of COVID-related deaths in the UK. 5 The UK COVIDsortium recruited a cohort of 731 HCW at three London hospitals early in the pandemic starting 23 rd March 2020 6 before the availability of vaccines.…”
Section: Introductionmentioning
confidence: 99%